Conceptualization of submerged structures as tsunami barrier - Jahromi, Bahman Esfandiar (Faculty of Civil Engineering, 2010)

(untitled)
On December 26, 2004 a devastating tsunami struck the west coast of peninsular malaysia. The island of penang was one of the places that suffered fromthe disaster. Fifty seven people died in thisarea when most of themwere enjoying their time on the beach.Many home appliances, several boats and fishing equipments were also destroyed in the area. In order to prevent similardamages froma possible recuning tsunami event, the steady-state spectralwave (stwave) model of surface water modelling system (sms) has been used to design a nearshore banier to dissipate the tsunami wave energy in this study,The december2004 tsunami was used as a reference case. Nearshore tsunami wave amplitude was obtainedfromfield surveying data conducted on july 9~ IOJ 2005. Whilst, offshore tsunami wave heightand directionhave been acquired from an output of tunami-n2 program. The model which has been calibrated against field survey data showed good agreement. Several breakwater layouts were simulated in the stwave model to derive an optimal configuration which could dissipate the tsunami wave energy before it reaches the penang island shoreline. From analysis made, it was found that eleven layouts reduced the tsunami wave heights by more than 70%. After extensive evaluation> breakwater layout number 39 was selected as the optimized layout showing the efficiency to reduce wave energy by 83%, At this efficiency, a wave height of 1.02 meter would impact the shorelineshoulda 6.0mtsunami wavewas made topropagate from offshore.